If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.14y + 0.07(y + 6000) = 1260 Reorder the terms: 0.14y + 0.07(6000 + y) = 1260 0.14y + (6000 * 0.07 + y * 0.07) = 1260 0.14y + (420 + 0.07y) = 1260 Reorder the terms: 420 + 0.14y + 0.07y = 1260 Combine like terms: 0.14y + 0.07y = 0.21y 420 + 0.21y = 1260 Solving 420 + 0.21y = 1260 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-420' to each side of the equation. 420 + -420 + 0.21y = 1260 + -420 Combine like terms: 420 + -420 = 0 0 + 0.21y = 1260 + -420 0.21y = 1260 + -420 Combine like terms: 1260 + -420 = 840 0.21y = 840 Divide each side by '0.21'. y = 4000 Simplifying y = 4000
| 12-3(4x+2)=3x+4(x-8) | | 3[x+5(6-x)+24]-11=79-15x | | 3-y=6y+7 | | 4(-18+24)= | | 2x-70=50+6x | | (-6+12i)(-7-9i)=0 | | 2x^3-3x=6x^2 | | 6r^2+12r+24=0 | | -(9-6a)-(10+5a)-14=-(2-6a)+(-a)+1 | | -5(n+4)+22=-3n-4 | | 15x-2(x+1)=154 | | 14x-4(4x-2)=5(2x+1)+3 | | 20.00-1.45*v=1.15 | | -9x-156=42-2x | | 14x-3(x+1)=96 | | 53=-16t^2+75t+30 | | 11x+9=4x+5 | | 4x^3+5x=13x^2 | | -[3x-(2x+6)]=-1-[3(2x-4)-3x] | | 8.12x+0.32=3.76x-3.23 | | 14x-3(x+1)=63 | | -10(s+3)=51 | | r^2+2r+4=0 | | y+6-10=0 | | 2/x+6=3/5x-11 | | 3x+3-4x=89 | | -10s+-30=51 | | 3x^3+5x^2=x | | 3.5x=y-7 | | 5.6-0.32*s=1.12 | | 8x+10-9x=89 | | 10.57x-16.75x+17.66=70.84 |